Comprehensive league table of cost-utility ratios: A systematic review of cost-effectiveness evidence for health policy decisions in India - Komal Shah; Malkeet Singh; Priya Kotwani; Kirti Tyagi; Apurvakumar Pandya; Somen Saha; Deepak Saxena; Kavitha Rajshekar (Frontiers Media S.A., 2022)
Background and objectivesAlthough a relatively recent concept for developing countries, the developed world has been using League Tables as a policy guiding tool for a comprehensive assessment of health expenditures; country-specific "League tables" can be a very useful tool for national healthcare planning and budgeting. Presented herewith is a comprehensive league table of cost per Quality Adjusted Life Years (QALY) or Disability Adjusted Life Years (DALY) ratios derived from Health Technology Assessment (HTA) or economic evaluation studies reported from India through a systematic review.MethodsEconomic evaluations and HTAs published from January 2003 to October 2019 were searched from various databases. We only included the studies reporting common outcomes (QALY/DALY) and methodology to increase the generalizability of league table findings. To opt for a uniform criterion, a reference case approach developed by Health Technology Assessment in India (HTAIn) was used for the reporting of the incremental cost-effectiveness ratio. However, as, most of the articles expressed the outcome as DALY, both (QALY and DALY) were used as outcome indicators for this review.ResultsAfter the initial screening of 9,823 articles, 79 articles meeting the inclusion criteria were selected for the League table preparation. The spectrum of intervention was dominated by innovations for infectious diseases (33%), closely followed by maternal and child health (29%), and non-communicable diseases (20%). The remaining 18% of the interventions were on other groups of health issues, such as injuries, snake bites, and epilepsy. Most of the interventions (70%) reported DALY as an outcome indicator, and the rest (30%) reported QALY. Outcome and cost were discounted at the rate of 3 by 73% of the studies, at 5 by 4% of the studies, whereas 23% of the studies did not discount it. Budget impact and sensitivity analysis were reported by 18 and 73% of the studies, respectively.Interpretation and conclusionsThe present review offers a reasonably coherent league table that reflects ICER values of a range of health conditions in India. It presents an update for decision-makers for making decisions about resource allocation.